1984
DOI: 10.1002/mpo.2950120111
|View full text |Cite
|
Sign up to set email alerts
|

Psychological aspects of patients in germ-free isolation: A review of child, adult, and patient management literature

Abstract: Life-threatening medical conditions such as severe combined immunodeficiency disease, leukemia, severe aplastic anemia, radiation injury, burns, organ transplantation, and aggressive administration of chemotherapy often necessitate the isolation of the patient in a protected germ-free environment for weeks or months. This treatment milieu has the effect of extensive psychological and physical isolation from family and staff. A review of the literature was undertaken to investigate the psychological implication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…(1994 ) support many of the previous research findings and also argue that patients in protective isolation develop symptoms of anxiety, depression, and cognitive disorders. Severe psychological reactions to protective isolation have also been reported by Lesko et al . (1984 ) and Kellerman et al .…”
Section: Related Literature On the Psychological Effects Of Isolationmentioning
confidence: 99%
“…(1994 ) support many of the previous research findings and also argue that patients in protective isolation develop symptoms of anxiety, depression, and cognitive disorders. Severe psychological reactions to protective isolation have also been reported by Lesko et al . (1984 ) and Kellerman et al .…”
Section: Related Literature On the Psychological Effects Of Isolationmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] To date, the responses of children to this stressful BMT environment have been described narratively and anecdotally, but there has been surprisingly little empiric data presented depicting patient response in pediatric BMT settings. A significant obstacle to the study of the acute psychosociaVsomatic effects of transplant has been a lack of appropriate measurement instruments.…”
Section: B Of'le Marrow Transplantationmentioning
confidence: 99%
“…Recent studies have indicated that quarantine during the SARS outbreak was an emotional and, for some, a financial hardship (Blendon, Benson, DesRoches, Raleigh, & Taylor‐Clark, 2004; Hawryluck et al, 2004). Although some researchers have investigated the psychological consequences of hospital isolation practices (Gammon, 1999; Lesko, Kern, & Hawkins, 1984), little is known about the subjective experience of quarantine, for example, how people manage protocols and the supports or barriers to compliance. We therefore undertook a descriptive, qualitative study to explore the experience of being quarantined, specifically the relationship between perceived risk of contracting SARS and reported compliance with the quarantine order and protocols.…”
mentioning
confidence: 99%